Golf styles and centre of pressure patterns when using different golf clubs - Ball, K. A.; Best, R. (Journal of Sports Sciences, 2011)
When using a driver, the centre of pressure of a golfer shows a pattern that is characteristic of one of two distinct swing styles: the "front foot" style or the "reverse" style. The aim of this study was to establish whether these two swing styles are also evident when using other clubs, and if so, to determine whether golfers use the same swing style when using different clubs. Forty-six professional, amateur, and recreational golfers performed swings to hit a ball into a net placed 3 m away. Ten swings were performed for each of the driver, 3-iron, and 7-iron while standing on two force plates. The position of the golfer's centre of pressure parallel with the line of shot and relative to the feet was quantified at eight swing events that were identified from 200-Hz video. Cluster analysis confirmed that the front foot and reverse styles were evident in all three clubs, and most of the golfers (96%) used the same swing style for all three clubs. Golfers that used the reverse swing positioned their centre of pressure nearer to their toes at ball contact compared with golfers that used the front foot swing.